Data Growth Identification and Application Performance Index (APDEX) Evaluation on the Performance of Geospatial Information Mapping Applications - Florence Elfriede Sinthauli Silalahi; Mugi Prayitno; Windy Gambetta; Fahmi Amhar; Tia Rizka Nuzula Rachma; Muhammad Nur Qomari Adi Wijaya (BBPSDMP KOMINFO MAKASSAR, 2021)
The Awareness for managing information technology (IT) as the responsibility of various parties has emerged, supported by improving in the quality of the Electronic Based Government System (SPBE), made IT cannot be considered as support only, but its strategic function is going started to be reviewed. This aims to realize the availability of data that is accurate, up-to-date, integrated, accountable, and easily accessible and shared by the public. Geospatial data and information (IG) are strategic because they are included in the implementation of the Presidential Decree One Data Indonesia together with statistical and financial data. GI that is generated and reprocessed from service systems and equipment sensors, requires operational management support, performance, and ease of addition, as well as interoperability with other systems. It is necessary to measure user satisfaction with GI services, namely in nine mapping applications, using the Application Performance Index (APDEX) Score using JMeter, identifying user behavior with Google Analytics, and recommending application performance improvements from the GT Metrix test results. From the results, the total number of application users is quite high. The APDEX score results show a range of 0.516 to 0.945, so improvements are needed for scripts, server utilization (CPU, memory, and storage), and available bandwidth. Furthermore, it is necessary to use a CDN or proxy to cache js, CSS scripts, and base maps (images), as well as optimize according to the recommendations of GT Metrix.